Free-electron creation at the 60° twin boundary in Bi2Te3 - Kwang-Chon Kim (Nature Portfolio, 2016)
Grain boundaries in polycrystalline materials may offer the opportunity to explore physical phenomena that do not normally occur within the crystal grains. Here, the authors show that twin boundaries in Bi2Te3works as an electron supply for the whole bulk material.